Pengaruh Model Problem Based Learning (PBL) Berbantuan Media Wordwall Terhadap Hasil Belajar Siswa pada Mata Pelajaran Informatika di SMAN 1 Gunung Talang - Malna, Annisya Ammelda; Zen, Zelhendri; Syafril, Syafril; Hendri, Nofri (Indo-MathEdu Intellectuals Journal, 2024)
This research is motivated by the low learning outcomes of students in Informatics subjects caused using a learning model that is still centered on teachers and the limited use of learning media. The purpose of this study is to find out whether there is an effect of the use of the Problem Based Learning (PBL) model assisted by wordwall media on student learning outcomes in informatics subjects at SMAN 1 Gunung Talang. The research was conducted using a quantitative method using Quasy Experimental Research. The population of this study is 305 students of class X with a sample of 50 students selected using the purposive sampling technique. Data analysis using t-test. The results of data analysis showed that the average post-test score of students in the experimental class was 78.40, while in the control class it was 64.68. Statistical testing shows that the tcount value of 10.78 exceeds the ttable value of 2.01 at a significant level α 0.05. Thus, it can be concluded that the problem-based learning model assisted by wordwalls has a significant impact on the learning outcomes of students in Informatics subjects at SMAN 1 Gunung Talang